Sex-specific effect of juvenile diet on adult disease resistance in a field cricket. - Clint D Kelly (Public Library of Science (PLoS), 2013)
Food limitation is expected to reduce an individual's body condition (body mass scaled to body size) and cause a trade-off between growth and other fitness-related traits, such as immunity. We tested the condition-dependence of growth and disease resistance in male and female Gryllus texensis field crickets by manipulating diet quality via nutrient content for their entire life and then subjecting individuals to a host resistance test using the live bacterium Serratia marcescens. As predicted, crickets on a high-quality diet eclosed more quickly, and at a larger body size and mass. Crickets on a high-quality diet were not in better condition at the time of eclosion, but they were in better condition 7-11 days after eclosion, with females also being in better condition than males. Despite being in better condition, however, females provided with a high-quality diet had significantly poorer disease resistance than females on a low-quality diet and in poor condition. Similarly, males on low- and high-quality diets did not differ in their disease resistance, despite differing in their body condition. A sex difference in disease resistance under diet-restriction suggests that females might allocate resources toward immunity during development if they expect harsh environmental conditions as an adult or it might suggest that females allocate resources toward other life history activities (i.e. reproduction) when food availability increases. We do not know what immune effectors were altered under diet-restriction to increase disease resistance, but our findings suggest that increased immune function might provide an explanation for the sexually-dimorphic increase in longevity generally observed in diet-restricted animals.